O passado, o presente e o futuro nas plantas Puruborá (Rondônia) - Menezes, Tarsila dos Reis (2016)
The intent of this work is to conduct an ethnographic study of the relationships between the Puruborá (a Tupi-speaking Amazonian group) from the village of Aperoí (state of Rondônia, Brazil) and plants, considering that this relationships permeates this people‟s ethnic reorganization based on the past and their keeping alive of what was taken from them, their traditional territory. Through the care of yards, it's remarkable the Puruborá‟s concern in maintaining them organized, clean, aesthetically beautiful and with appropriately cultivated plants. To the Puruborá, it's an imperative to keep a clean yard. The large variety of plants that circulate throughout the many village‟s yards is a reflection of the diversity of species within each area. The search for new and renewed of plants in the village of Aperoí is a never-ending task. According to the Puruborá, the Cigana area (their former traditional territory) once had even more plant diversity than Aperoí does today. Therefore, the plants create a connection between past and present, but also with the future. I say “future” because they are included in the prosperous plans of reforesting the village after official territorial demarcation: “Here‟s going to be like it used to be in Cigana”.